2015
DOI: 10.1007/s11749-015-0449-z
|View full text |Cite
|
Sign up to set email alerts
|

On optimum life-testing plans under Type-II progressive censoring scheme using variable neighborhood search algorithm

Abstract: In determination of optimum Type-II progressive censoring scheme, the experimenter needs to carry out an exhaustive search within the set of all admissible censoring schemes. The existing recommendations are only applicable for small sample sizes. The implementation of exhaustive search techniques for large sample sizes is not feasible in practice. In this article, a meta-heuristic algorithm based on variable neighborhood search approach is proposed for large sample sizes. It is found that the algorithm gives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Observe that for a given value of n and m, a total of ð nÀ1 mÀ1 Þ choices are available to select a scheme R ¼ ðR 1 ; RÀ2; :::; R m Þ such that P m i¼1 R i ¼ ðnÀmÞ. Thus, searching an optimal scheme among all possible schemes may be computationally inconvenient for higher values of n and m. Recently, Bhattacharya et al (2016) proposed a meta heuristic based variable neighborhood search (VNS) algorithm which is quite useful in constructing optimal plans for moderate to large values of n and m. The main advantage of using VNS algorithm is that it provides near optimal solution with relatively less computation time. Construction of optimal plans under hybrid censoring is equivalent to selecting the values of m and T based on a given optimal criterion, and one may refer to Dube et al (2011) for optimal hybrid censoring plans for a lognormal distribution.…”
Section: Optimal Censoringmentioning
confidence: 99%
“…Observe that for a given value of n and m, a total of ð nÀ1 mÀ1 Þ choices are available to select a scheme R ¼ ðR 1 ; RÀ2; :::; R m Þ such that P m i¼1 R i ¼ ðnÀmÞ. Thus, searching an optimal scheme among all possible schemes may be computationally inconvenient for higher values of n and m. Recently, Bhattacharya et al (2016) proposed a meta heuristic based variable neighborhood search (VNS) algorithm which is quite useful in constructing optimal plans for moderate to large values of n and m. The main advantage of using VNS algorithm is that it provides near optimal solution with relatively less computation time. Construction of optimal plans under hybrid censoring is equivalent to selecting the values of m and T based on a given optimal criterion, and one may refer to Dube et al (2011) for optimal hybrid censoring plans for a lognormal distribution.…”
Section: Optimal Censoringmentioning
confidence: 99%
“…Kundu (2009, 2013) proposed criterion based on asymptotic variance of estimated pth quantile of the underlying lifetime distribution and obtained the optimal censoring schemes for generalized exponential and Birnbaum-Saunders distributions. Bhattacharya et al (2016) introduced a meta-heuristic algorithm, called variable neighborhood search (VNS), for the determination of optimal censoring schemes. They showed that the VNS algorithm performs sufficiently well for moderate to large values of n and m. Recently, Bhattacharya (2020) introduced the notion of compound optimal design strategy under progressive censoring in a multi-criteria setup.…”
Section: Introductionmentioning
confidence: 99%
“…For concise reviews and resources on planning, modeling, and analyzing the step‐stress ALT, readers are referred to Nelson, Meeker and Escobar, Bagdonavicius and Nikulin, Collins et al, and Limon et al Furthermore, due to time and resource constraints, censored sampling is usually necessary in practice, and in particular, a generalized censoring scheme known as progressive type I censoring allows functional test units to be withdrawn successively from the experiment at some prefixed nonterminal time points. Those withdrawn unfailed units can be used in other tests in the same or at a different facility; see, for instance, Cohen, Lawless, and Balakrishnan et al Despite its flexibility and efficient utilization of the available resources compared with the conventional sampling methods, progressively censored sampling has not gained much popularity in ALT, partly due to its complicated likelihood function rendering its statistical analysis rather difficult or mathematically intractable; see Balakrishnan, Pradhan and Kundu, Cramer and Iliopoulos, and Bhattacharya et al …”
Section: Introductionmentioning
confidence: 99%